THE EFFECT OF BETA DETERMINATION ON THE PERFORMANCE OF SHARIA AND NON-SHARIA STOCK PORTFOLIOS USING THE REWARD TO DIVERSIFICATION APPROACH: A STUDY OF THE INDONESIAN STOCK EXCHANGE - Tania, Atika; Evana, Einde; Prasetyo, Trijoko (Politeknik Negeri Ambon, 2025)
Introduction: Islamic finance is growing rapidly worldwide, as evidenced by the performance of sharia-compliant indices in countries such as Bangladesh and the Dow Jones Islamic Index. The number of Sharia stock investors in Indonesia is also increasing; therefore, it is vital to understand the performance of Sharia stock portfolios and the systemic risks that affect them. The purpose of this study is to examine the effect of beta on the performance of Sharia and non-Sharia stock portfolios in Indonesia.Methods: The research method used is quantitative, with data sources from Yahoo Finance and the IDX website. Beta is a systematic risk that determines the level of portfolio return. The betas used are market beta, accounting beta, fundamental beta, and macroeconomic beta.Results: The simultaneous multiple linear regression indicates that beta has a significant effect on stock portfolio performance. Meanwhile, accounting beta and fundamental beta partially affect the performance of Sharia stock portfolios, while fundamental beta and macroeconomic beta affect the performance of non-Sharia stock portfolios. The difference test between the two performances shows that there is no significant difference between Sharia and non-Sharia stocks. Keywords: Systemic risk, Return, Stock Portfolio Performance